Afterlife (Colorado State Library Book Club Collection): a novel (Algonquin Books of Chapel Hill, 2021)
"A literature professor tries to rediscover who she is after the sudden death of her husband, even as a series of family and political jolts force her to ask what we owe those in crisis in our families, biological or otherwise"--
Prologue : broken English , Here there be dragons , Where is Burkina Faso? , Rules of sisterhood , To be missing is not a crime , Bar a luz , Who is the most important one? , Objects in mirror are closer than they appear , All it takes , Air quotes , Cuckoos in Kyoto , As if , Harvest , Epilogue : Japanese repair technique.

In the time of the butterflies (Colorado State Library Book Club Collection) (Algonquin Books of Chapel Hill, 2019)
"Set during the waning days of the Trujillo dictatorship in the Dominican Republica in 1960, this extraordinary novel tells the story the Mirabal sisters, three young wives and mothers who are assassinated after visiting their jailed husbands."--Provided by publisher "It is November 25, 1960, and three sisters have been found near their wrecked Jeep at the bottom of a 150-foot cliff on the north coast of the Dominican Republic. The official state newspaper reports their deaths as accidental. It does not mention that a fourth sister lives. Nor does it explain that the young women were among the leading opponents of General Rafael Leonidas Trujillo dictatorship. It doesn't have to. Everybody knows of Las Mariposas-- the Butterflies." In this extraordinary novel, the voices of all four sisters--Minerva, Patria, María Teresa, and the survivor, Dedé--speak across the decades to tell their own stories, from hair ribbons and secret crushes to gunrunning and prison torture, and to describe the everyday horrors of life under Trujillo's rule. Through the art and magic of Julia Alvarez's imaginative storytelling, the martyred Butterflies live again in this novel of courage, love, and the human cost of political oppression"-- Back Cover An ALA Notable Book. Julia Alvarez's eagerly awaited second novel is a powerful story of courage, innocence, and political martyrdom in the Hispanic Caribbean. Based on actual events--the death of three sisters on November 25, 1960--the novel immerses us in an epoch in the life of the Dominican Republic. The "Butterflies," as they were known, lived daringly and dangerously under a regime that imprisoned, tortured, and killed with impunity. -- Publisher description
Dede, 1994 and circa 1943 , Minerva, 1938, 1941, 1944 , Maria Teresa, 1945 to 1946 , Patria, 1946 , Dede, 1994 and 1948 , Minerva, 1949 , Maria Teresa, 1953 to 1958 , Patria, 1959 , Dede, 1994 and 1960 , Patria, January to March 1960 , Maria Teresa, March to August 1960 , Minerva, August to November 25, 1960 , Epilogue: Dede, 1994 , A Postscript.

Antes de ser libres (Colorado State Library Book Club Collection) (Ember, 2018)
In the early 1960s in the Dominican Republic, twelve-year-old Anita learns that her family is involved in the underground movement to end the bloody rule of the dictator, General Trujillo.

En el tiempo de las mariposas (Colorado State Library Book Club Collection) (Plume, 2001)
Gives a fictionalized account of four sisters in the Dominican Republic under the dictatorship of General Trujillo.

Más Allá (Colorado State Library Book Club Collection): una novela (Vintage Español, una división de Penguin Random House LLC, 2020)
Una profesora de literatura intenta redescubrir quién es después de la repentina muerte de su marido, incluso cuando una serie de sacudidas familiares y políticas la obligan a preguntarse qué debemos a los que están en crisis en nuestra familia, biológicos o de otro tipo.